New insights into intra- and intermolecular interactions of immunoglobulins: crystal structure of mouse IgG2b-Fc at 2.1-A resolution - Kolenko, Petr; Dohnálek, Jan; Dušková, Jarmila; Skálová, Tereza; Collard, Renata; Hašek, Jindřich (Immunology, 2009)
The structure of the Fc fragment of monoclonal antibody IgG2b from hybridom M75 of Mus musculus has been determined by single crystal X-ray diffraction. This is the first report of the structure of the murine immunoglobulin isotype IgG2b. The structure refined at 2.1 A resolution provides more detailed structural information about native oligosaccharides than was previously available. High-quality Fourier maps provide a clear identification of alpha-l-fucose with partial occupancy in the first branch of the antennary oligosaccharides. A unique Fc:Fc interaction was observed at the C(H)2-C(H)3 interface.
Keywords: imunoglobuliny - Fc fragmenty; Animals; Immunoglobulin G; Financing, Organized; glykosylace; krystalizace; Protein Structure, Secondary; krystalografie rentgenová; Immunoglobulin Fc Fragments; Glycosylation; monoklonální protilátky; oligosacharidy; Antibodies, Monoclonal; zvířata; financování organizované; myši; Oligosaccharides; imunokomplex; Crystallography, X-Ray; imunoglobulin G; Crystallization; sekundární struktura proteinů; Antigen-Antibody Complex; Mice